Blowing up Russia the secret plot to bring back KGB terror : acts of terror, abductions, and contract killings organized by the Federal Security Service of the Russian Federation - Litvinenko, Aleksandr V. 1962-2006; Felʹštinskij, Jurij Georgievič 1956- (Gibson Square, 2007)
'Blowing Up Russia' contains the attacks of ex-spy Alexander Litvinenko against his former spymasters in Moscow which led to his being murdered in London by poisoning. Litvinenko and Yuri Felshtinsky detail how, since 1999, the secret service has been hatching a secret plot to return to the terror that was the hallmark of the KGB.
Includes index
Keywords: Russland -- Federalʹnaja služba bezopasnosti; Geschichte 1994-2005; Tschetschenienkriege; Verschwörung; Politische Verfolgung; Russland; Secret service / Russia (Federation); State-sponsored terrorism / Russia (Federation); Abuse of administrative power / Russia (Federation); Russia (Federation) / Politics and government / 1991-; Abuse of administrative power; Politics and government; Secret service; State-sponsored terrorism; Russia (Federation); Since 1991